2009
DOI: 10.1002/eji.200838676
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of macrophage activation and septic shock susceptibility via p21(WAF1/CIP1)

Abstract: p21 is a cell-cycle inhibitor that is also known to suppress autoimmunity. Here, we provide evidence of a novel role for p21 as an inhibitor of macrophage activation. LPS stimulation of p21-deficient peritoneal macrophages induced increased activation compared with controls, with elevated production of proinflammatory mediators such as TNF-a and IL-1b. The enhanced activity of LPS-stimulated p21-deficient macrophages correlated with increased activity of the transcription factor NF-jB. LPS stimulation of p21-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 39 publications
9
66
0
Order By: Relevance
“…Waf1 is a negative regulator that curbs excessive macrophage activation by providing a negative feedback system of TNF-a and IL-1b production (38,39). We propose a similar function for Trex1 as macrophage controller of activation.…”
Section: Discussionmentioning
confidence: 92%
“…Waf1 is a negative regulator that curbs excessive macrophage activation by providing a negative feedback system of TNF-a and IL-1b production (38,39). We propose a similar function for Trex1 as macrophage controller of activation.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, p53 and p21 are reported to be antiinflammation factors (27)(28)(29). Furthermore, p21 is a negative regulator of macrophage activation; in particular, it inhibits the lipopolysaccharide-dependent stimulation of TNF-α and IL-1β (29,30). Moreover, the inhibition caused by p21 inhibits the NF-κB activity (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p21 is a negative regulator of macrophage activation; in particular, it inhibits the lipopolysaccharide-dependent stimulation of TNF-α and IL-1β (29,30). Moreover, the inhibition caused by p21 inhibits the NF-κB activity (29,30). Yanaka et al (7) reported the inhibitory effect of PL on the lipopolysaccharide-dependent activation of NF-κB in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated NF-κB activity and secretion of cytokines was also found in LPSstimulated p21-deficient mouse and human macrophages as compared to similarly treated wild-type cells. 82,83 It will be interesting to learn whether the increased inflammatory status of p21-/-mice is p53 dependent.…”
Section: P53 As An Inhibitor Of Inflammationmentioning
confidence: 99%